HyTest: Platform for Structural Hybrid Simulations with Finite Element Model Updating. (October 2017) - Yang, Ge; Wu, Bin; Ou, Ge; Wang, Zhen; Dyke, Shirley
Highlights: First, an identification module is developed to implement the UKF method together with OpenSees. The source code of OpenSees is modified to provide a time-efficient procedure to conduct the repeated evaluations for multiple sampled parameters. Second, all the constitutive models on any level (material, sectional, or element level) within the framework of OpenSees can be updated using HyTest. Hence, this research can help broaden the utilization of hybrid simulation with model updating to sophisticated finite element structural models. Abstract: Hybrid simulation has been demonstrated to be a powerful method to evaluate the system-level dynamic performance of structure. With the numerical substructure analyzed with finite element software and the difficult-to-model components tested with an experimental substructure, complex structures with sophisticated behaviors can readily be examined through a hybrid simulation. To coordinate and synchronize the substructures in hybrid simulation, software is required. In recent studies, model updating has been integrated into hybrid simulation to improve testing accuracy by updating the numerical model during the analysis. However, online model updating scheme requires some modifications in the typical hybrid simulation testing procedure, and this greater complexity is entailed in its implementation regarding the collaboration of identification algorithms with existing hybrid simulation software. To address this issue and broaden the utilization of hybrid simulation with model updating, an existing platform named HyTest originally for conventional hybrid simulation is extended for this purpose. This version of HyTest facilitates the online identification of material constitutive parameters using experimental measurements in its finite element based identification module. It also includes a data center with a uniform data transmission protocol to incorporate different substructures and modules. A numerical example is used to demonstrate the online identification of material parameters for concrete and steel models in a reinforced column, and to verify the accuracy of the identification module. Lastly the effectiveness of HyTest in conducting hybrid simulation with model updating is validated using actual hybrid tests on a steel frame.